Find the ordered pair solution to the following system of equations 3x – y = 2
y = 4x – 3

3x – y = 2 y = 4x – 3 3x – (4x – 3) = 2; 3x - 4x + 3 = 2; -x + 3 = 2; -x = 2 - 3; -x = -1; x = 1; y = 4(1) – 3; y = 4 - 3; y = 1 The solution set is (1, 1).

Question

Asked 2/22/2013 12:33:43 AM

Updated 4/7/2015 4:12:37 AM

1 Answer/Comment

Edited by Andrew. [4/7/2015 4:12:35 AM]

Rating

3

3x – y = 2

y = 4x – 3

3x – (4x – 3) = 2;

3x - 4x + 3 = 2;

-x + 3 = 2;

-x = 2 - 3;

-x = -1;

x = 1;

y = 4(1) – 3;

y = 4 - 3;

y = 1

The solution set is (1, 1).

y = 4x – 3

3x – (4x – 3) = 2;

3x - 4x + 3 = 2;

-x + 3 = 2;

-x = 2 - 3;

-x = -1;

x = 1;

y = 4(1) – 3;

y = 4 - 3;

y = 1

The solution set is (1, 1).

Added 4/7/2015 4:12:37 AM

This answer has been confirmed as correct and helpful.

Given the function f(x) = - 2x , find the value of f(–1). **Weegy:** y+4=2x (More)

Question

Expert Answered

Updated 4/7/2015 4:13:38 AM

1 Answer/Comment

f(x) = - 2x;

f(-1) = -2(-1);

f(-1) = 2

f(-1) = -2(-1);

f(-1) = 2

Added 4/7/2015 4:13:38 AM

This answer has been confirmed as correct and helpful.

For f(x) = -x^2 -x + 5, find f(-3) **Weegy:** (More)

Question

Expert Answered

Updated 14 days ago|7/5/2018 6:19:48 AM

1 Answer/Comment

f(x) = -x^2 - x + 5, find f(-3)

f(-3) = -(-3)^2 - (-3) + 5

f(-3) = -9 + 3 + 5

f(-3) = -6 +5

f(-3) = -1

f(-3) = -(-3)^2 - (-3) + 5

f(-3) = -9 + 3 + 5

f(-3) = -6 +5

f(-3) = -1

Added 14 days ago|7/5/2018 6:19:47 AM

This answer has been confirmed as correct and helpful.

When a variable loses its scope, its data value is not lost. True or False?

Question

Expert Answered

Updated 1/23/2017 9:26:50 AM

1 Answer/Comment

Cloaking a file is the same as ___________.

Question

Expert Answered

Updated 159 days ago|2/10/2018 10:38:25 AM

1 Answer/Comment

Cloaking a file is the same as HIDING the file.

Added 159 days ago|2/10/2018 10:38:25 AM

This answer has been confirmed as correct and helpful.

27,097,791

questions answered

There are no comments.